Political Economy of the Public Forest Certification in the Gunungkidul Regency, DIY Province - SULISTYANINGSIH, SULISTYANINGSIH (Universitas Muhammadiyah Yogyakarta, 2013)
Public forests, particularly the ones in Java island, were developed in the 1930s by Dutch colonialgovernment although the government’s policy did not fully recognize and legitimate them as state forests.Nevertheless, the contribution of the forests to local communities cannot be denied, because the existenceof community forest can be lifesaving. That public forest after deforestation becomes an alternativesolution can be seen in changes in the timber industry, in that demand for wood is increasing. The changeresulted could be seen in the cultural change of this industry on the management of public forest in Java,especially in Gunungkidul Yogyakarta. The demand and pressure of international market that setrequirements on the wood sold to be of high quality and accompanied with legal documents of publicforets is an absolute condition to have the logs be accepted, recognized and marketed in internationalmarket. In political economical context, forest certification in Gunungkidul regency needs theintervention of the State to protect the marketing of timber from public forests.